2022
DOI: 10.3233/jad-220479
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium breve MCC1274 Supplementation Increased the Plasma Levels of Metabolites with Potential Anti-Oxidative Activity in APP Knock-In Mice

Abstract: Background: We previously reported the effects of a probiotic strain, Bifidobacterium breve MCC1274, in improving cognitive function in preclinical and clinical studies. Recently, we demonstrated that supplementation of this strain led to decreased amyloid-β production, attenuated microglial activation, and suppressed inflammation reaction in the brain of APP knock-in (App NL - G - F ) mice. Objective: In this study, we investigated the plasma metabolites to reveal the mechanism of action of this probiotic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…These changes were associated with increased regulation of gut microbiota composition and improvement in intestinal barrier function [ 89 ], highlighting the therapeutic potential of GBA modulation. Another study similarly reported Bifidobacterium breve supplementation in amyloid beta precursor protein (APP) knock-in mice increased the bioavailability of anti-oxidative metabolites, which improved cognitive function [ 90 ]. Huang et al [ 91 ] demonstrated that the use of Lactobacillus plantarum can delay AD progression by regulating gliosis and tau hyperphosphorylation following a reduction in propionic acid levels.…”
Section: Gut-microbiota-modulating Agents In Amyotrophic Lateral Scle...mentioning
confidence: 99%
“…These changes were associated with increased regulation of gut microbiota composition and improvement in intestinal barrier function [ 89 ], highlighting the therapeutic potential of GBA modulation. Another study similarly reported Bifidobacterium breve supplementation in amyloid beta precursor protein (APP) knock-in mice increased the bioavailability of anti-oxidative metabolites, which improved cognitive function [ 90 ]. Huang et al [ 91 ] demonstrated that the use of Lactobacillus plantarum can delay AD progression by regulating gliosis and tau hyperphosphorylation following a reduction in propionic acid levels.…”
Section: Gut-microbiota-modulating Agents In Amyotrophic Lateral Scle...mentioning
confidence: 99%
“…A recent study, for example, looked at the postbiotic potential of L. plantarum metabolites, finding that they can boost the production of short-chain fatty acids, which are known to support intestinal epithelial integrity ( Markowiak-Kopeć and Śliżewska, 2020 ). Furthermore, research on metabolites produced from B. breve exhibited potential in controlling glucose metabolism ( Ohno et al, 2022 ). Integrating postbiotics into functional foods and beverages, such as yogurt, fermented drinks, or even snacks, is an innovative strategy for delivering these health advantages in a practical and pleasant way ( Thorakkattu et al, 2022 ).…”
Section: Applications Of Postbioticsmentioning
confidence: 99%
“…Furthermore, treating APPKI mice (AppNL-G-F) with the same probiotic reduced amyloid plaque deposition, increased alpha-secretase expression, and decreased microglial cell activation [ 26 ]. Plasma metabolomics analysis of these mice indicated that MCC1274 consumption increased the levels of several metabolites with known activity against oxidative stress, as well as metabolites related to the mitochondrial TCA cycle, although the specific metabolite(s) responsible for these effects were not identified [ 27 ]. In the present study, we asked whether other metabolites generated by this probiotic prevent the inflammation-derived oxidative stress and lipid droplet formation that occur in MCI and Alzheimer’s disease by controlling perilipin gene expression.…”
Section: Introductionmentioning
confidence: 99%